Interference Effect of Submerged Pipeline on the Scour Depth of Isolated Bridge Pier on a Mobile Bed - Malik, Rahul; Setia, Baldev (International Journal of Advanced Science and Technology, 2019)
Pipelines are used to transport water, distilled petroleum, and some other liquid over the waterway are mostly part covered under the sediment bed. Cooperation between a submerged pipeline and the portable bed accept significance in engineering in light of the surprising expense of laying such pipelines. The pipelines may turn out to be mostly presented to the activity of water flows where the flood causes a general scour in the bed of the waterway. Additionally, as an immediate results of fast urbanization, bridges in close proximity are probably going to meddle with such pipelines improving their defenselessness to scour. It is concurred that the distinction in pressure on the upstream side and downstream side of the pipe start the piping action underneath the pipeline. Pipeline together with stagnation vortex join to decide the pipeline and imprint the beginning of scour. Maximum scour beneath the pipeline observe when there is a little hole between the pipe line and the undisturbed bed. As the hole expands, scour profundity step by step diminishes. For a pipeline set at bed level, temperamental stream as hydrograph gives more scour than that for a uniform stream. Segment like transitional backings gave underneath the pipeline and extension in nearness is probably going to build the scour extensively.